Rerouting the Pathway for the Biosynthesis of the Side Ring System of Nosiheptide: The Roles of NosI, NosJ, and NosK - Badding, Edward D. (J Am Chem Soc, 2017)
[Image: see text] Nosiheptide (NOS) is a highly modified thiopeptide antibiotic that displays formidable in vitro activity against a variety of Gram-positive bacteria. In addition to a central hydroxypyridine ring, NOS contains several other modifications, including multiple thiazole rings, dehydro-amino acids, and a 3,4-dimethylindolic acid (DMIA) moiety. The DMIA moiety is required for NOS efficacy and is synthesized from l-tryptophan in a series of reactions that have not been fully elucidated. Herein, we describe the role of NosJ, the product of an unannotated gene in the biosynthetic operon for NOS, as an acyl carrier protein that delivers 3-methylindolic acid (MIA) to NosK. We also reassign the role of NosI as the enzyme responsible for catalyzing the ATP-dependent activation of MIA and MIA’s attachment to the phosphopantetheine moiety of NosJ. Lastly, NosK catalyzes the transfer of the MIA group from NosJ-MIA to a conserved serine residue (Ser102) on NosK. The X-ray crystal structure of NosK, solved to 2.3 Å resolution, reveals that the protein is an α/β-fold hydrolase. Ser102 interacts with Glu210 and His234 to form a catalytic triad located at the bottom of an open cleft that is large enough to accommodate the thiopeptide framework.